Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 7 - Exponential Functions - 7.6 Models Involving y'=k(y-b) - Preliminary Questions - Page 359: 3



Work Step by Step

The solution of $y'=-k(y-b)$ is $$y=b+c e^{-kt}.$$ Since $k\gt 0$, then as $t\to \infty$, then $y\to b$ and hence all solutions will tend to $\infty$ as $t\to \infty$. So the statement is true.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.